PERAWATAN RONGGA MULUT PASIEN BELL’S PALSY: LAPORAN KASUS - Fadhilah, Fania; Fauziah, Hana; Aziza, Fidela Dwirahma; Nur'aeny, Nanan (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Bell’s palsy (BP) is an acute weakness or paralysis of the peripheral fascial nerve with an incidence of approximately 20–30 per 100,000 individuals. Bell’s palsy is characterized by a droopy appearance on one side of the face and the inability to open or close the eyes on one side. This condition can affect limitations in daily activities such as eating, drinking, and speaking, as well as the oral health of the sufferer. Patients with Bell’s palsy can have a high caries risk due to decreased saliva production and angular cheilitis. The purpose of this case report is to determine the relationship between the oral manifestations experienced by patients with Bell’s palsy and appropriate management. Case and Management: A 54-year-old woman came with complaints of mouth discomfort. Two weeks earlier, the patient felt that her mouth was left-sided and had received treatment from a neurologist, currently it has improved but still feels numb. There was no history of dental disease or allergies. Extraoral examination: the face was symmetrical, and there were brownish macules, multiple, about 1-2 mm in size, painless. Intraoral examination: The lips were dry, and there was a brownish macule on the lower lip, an irregular shape, a size of about 1cm, no pain, and a deviation of about 1-2 mm to the left on the lower lip. The white plaque on the entire surface of the tongue dorsum could be scraped and did not leave red areas. There was a longitudinal gap in the center of the tongue dorsum and an indentation on the lateral tongue. The patient was instructed to maintain oral hygiene, prescribed povidone iodine 1% as an antiseptic, vaseline album to treat dry lips, neurobion tablets, and consultation with a neurologist. Conclusion: The patient's clinical condition is mild, but oral care for BP patients is very important to maintain oral hygiene